Diagnostic value of SARS-CoV-2 RDT-Ab with RT-PCR: Secondary data at Diponegoro National Hospital - Muhammad Thifan Satyagraha; Nani Maharani; Rebriarina Hapsari; Meita Hendrianingtyas (Journal of Biomedicine and Translational Research, 2022)
Background: The SARS-CoV-2 rapid diagnostic test antibody (RDT-Ab) was most often used as an early detection tool for COVID-19 at the beginning of pandemic. Whereas the antibody response was formed in the second week after the onset of symptoms.Objective: To evaluate the diagnostic value of the SARS-CoV-2 RDT-Ab, including sensitivity (Se), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), and negative likelihood ratio (NLR), in patients at Diponegoro National Hospital, Semarang, Indonesia.Methods: Data subjects have been selected retrospectively using purposive sampling based on inclusion criteria (patients who had shortness of breath, pneumonia, suspected, possible, or confirmed COVID-19, and data on the results of the SARS-CoV-2 RDT-Ab IgM and/or IgG (Leccurate® SARS-CoV-2 Antibody Rapid Test Kit) with a valid RT-PCR as gold standard) and exclusion criteria (patients who only had one of either SARS-CoV-2 RDT-Ab or RT-PCR). Researchers analyzed the diagnostic value of SARS-CoV-2 RDT-Ab with RT-PCR which gave the possibility of true-positive, false-positive, true-negative, and false-negative results arranged in a 2x2 table. According to WHO, the diagnostic value is said to be good at least having a sensitivity value of 80% and specificity of 97%.Results: The diagnostic value of SARS-CoV-2 RDT-Ab with RT-PCR, which was evaluated from 1142 patients retrospectively, included IgM (Se 65.25%, Sp 89.51%, PPV 46.70%, NPV 94.81%, PLR 6.22, NLR 0.39), IgG (Se 58.16%, Sp 93.01%, PPV 53.95%, NPV 94.04%, PLR 8.32, NLR 0.45), IgM and IgG (Se 53.90%, Sp 94.21%, PPV 56.72%, NPV 93.55%, PLR 9.30, NLR 0.49), IgM and/or IgG (Se 69.50%, Sp 88.31%, PPV 45.58%, NPV 95.36%, PLR 5.95, NLR 0.35).Conclusion: SARS-CoV-2 RDT-Ab (Leccurate® SARS-CoV-2 Antibody Rapid Test Kit) is not ideal to be used as a rapid diagnostic test for COVID-19.Keywords: COVID-19, Rapid diagnostic test, RT-PCR, SARS-CoV-2 antibody